PERAN EDUKASI GURU SEKOLAH DALAM PEMBENTUKAN LITERASI KESEHATAN REMAJA PUTRI TENTANG TABLET TAMBAH DARAH - Yulianti, Desak Made; Delvia Pombaile, Veny; Susanti Papuke, Sri; Nurhidayah, Nurhidayah; Alza, Nurfaizah (Jurnal Stunting Pesisir dan Aplikasinya, 2026)
ABSTRACT Introduction: Iron deficiency anemia remains a major public health problem among adolescent girls aged 10–19 years, with wide-ranging impacts on physical health, cognitive function, and academic achievement. Iron supplementation through iron tablets is an important strategy for anemia prevention; however, its effectiveness is strongly influenced by adolescents’ levels of knowledge and attitudes. In the school context, teachers play a strategic role as educational agents in shaping students’ health literacy. This study aims to analyze the relationship between teachers’ educational roles and the knowledge and attitudes of adolescent girls regarding iron tablet supplementation at SMP Negeri 12 Gorontalo City. Method: This study employed a quantitative observational design with a cross-sectional approach. The study population consisted of all female students in grades VII and VIII at SMP Negeri 12 Gorontalo City. A total of 80 adolescent girls were included as the sample. Data were collected using a structured questionnaire and analyzed using the Kruskal–Wallis test. Results: Among the 80 respondents, the analysis showed that the relationship between teachers’ roles and adolescent girls’ knowledge and attitudes toward iron tablet supplementation differed by grade level. In grade VII, teachers’ roles were significantly associated with knowledge levels (p = 0.042; p < 0.05), but not with attitudes (p = 0.620; p > 0.05). In contrast, in grade VIII, teachers’ roles were not significantly associated with either knowledge (p = 0.093) or attitudes (p = 0.353). These findings indicate that the influence of teachers’ roles is more evident in the cognitive aspects of students at the lower grade level. Conclusion: There is a significant relationship between teachers’ educational roles and the knowledge of grade VII adolescent girls, but not among grade VIII students, and no significant association was found with attitudes at either grade level